COLLISION PROBABILITY OF AIRCRAFT FLYING ON PARALLEL TRACKS - Kharchenko, Volodymyr; Alexeiev, Oleg; Tapia, Katerina (Proceedings of National Aviation University, 2013)
Concepts of Air Traffic Management are focused on the geometry of airways. Today’s navigation facilities are able to increase airspace capacity due to more accurate path keeping and providing reduced position error. It will increase capacity of airspace but decrease safety level. According to this collision probability between two aircraft flying on opposite tracks with reduced lateral separation is considered and compared with level of safety.